(untitled) (Circe de clásicos y modernos, 2025)
The character of the maid is a figure with a relative presence in the comic theatre of Classical Antiquity. From Aristophanes to Menander, from Plautus to Terence, next to the mistress of the house or the young woman in love is, as a rule, the accomplice and faithful female-slave. How does Camões recover and recreate this feminine type in his pieces? Does it rework the traces of Greco-Latin convection? Or, on the contrary, does it redesign the character of the maid, readjusting it to the social circumstances of his time and to the respective artistic-literary dictates? In this article, we intend to answer these questions, through a textual analysis that highlights the common and divergent points between the models bequeathed by the tradition of yesteryear and the maids that intervene in the plots of the three plays written by Camões.